Numerical Analysis of Fluid Flow on Cross Flow and Kaplan Turbine Prototype - Purwantono, Purwantono; Sidiq, Ahmad Halim; Irzal, Irzal; Refdinal, Refdinal (Universitas Negeri Padang, 2018)
Based on previous research conducted by Purwantono about the utilization of exhaust flow from a conventional cross-flow turbine prototype that was used as an inlet of tubin Kaplan [1]. This research was carried out to see how the exhaust flow velocity of each tubin before and after was combined into one combination turbine. This numerical based study uses the Ansys 18.0 application by inputting a 3D design from a conventional turbine prototype which was used as the material for this study. The results obtained in this study show the average of outlet velocity in the Kaplan turbine that uses a velocity outlet from a cross flow turbine of 0.3 m / s greater when it is combined, which is 8.33 m / s and after being combined to 0.38 m / s. The results of this study are expected to contribute to the development of conventional turbines later